Web-Based Asynchronous Teleconsulting for Consumers in Colombia: A Case Study - Valenzuela, José Ignacio; Arguello, Arturo; Cendales, Juan Gabriel; Rizo, Carlos A (JMIR Publications, 2007)
Background Fourteen years after the reform to Colombia's health system, the promises of universality, improved equity, efficiency, and better quality of care have not materialized. Remote areas remain underserved and access to care very limited. Recognizing teleconsultation as an effective way to improve access to health care and health information, a noncommercial open-access Web-based application for teleconsultation called Doctor Chat was developed. Objective The objective was to report the experience of the Center for Virtual Education and Simulation eHealth (Centro de Educación Virtual y Simulación e-Salud) with open-access Web-based asynchronous teleconsultation for consumers in Colombia. Methods A teleconsultation service in Spanish was developed and implemented in 2006. Teleconsultation requests were classified on three axes: (1) the purpose of the query, (2) the specialty, and (3) the geographic area of the query. Content analysis was performed on the free-text queries submitted to Doctor Chat, and descriptive statistics were gathered for each of the data categories (name, email, city, country, age, and gender). Results From September 2006 to March 2007, there were 270 asynchronous teleconsultations documented from 102 (37.8%) men and 168 (62.2%) women. On average, 1.4 requests were received per day. By age group, the largest number of requests (n = 80; 30%) were from users 24-29 years, followed by users (n = 66; 24%) 18-23 years. Requests were mainly from Colombia (n = 204; 75.6%) but also from Spain (n = 17; 6.3%), Mexico (n = 11; 4.1%), and other countries. In Colombia, 137 requests (67.2%) originated in Bogotá, the nation's capital, 25 (12.4%) from other main cities of the country, 40 (19.7%) from intermediate cities, and 2 (0.7%) from remote areas. The purpose of the majority of requests was for information about symptoms, health-related problems, or diseases (n = 149; 55.2%) and medications/treatments (n = 70; 25.9%). By specialty, information was most requested for gynecology and obstetrics (n = 71; 26%), dermatology (n = 28; 10%), urology (n = 22; 8%), and gastroenterology (n = 18; 7%), with anesthesiology, critical care, physical medicine and rehabilitation, and pathology being the least requested (n = 0; 0%). Overall, sexual and reproductive health (n = 93; 34%) issues constituted the main query subject. The average time to deliver a response was 120 hours in 2006 and 59 hours in 2007. Only 19 out of 270 users (7%) completed a survey with comments and perceptions about the system, of which 18 out of 19 (95%) corresponded to positive perceptions and 1 out of 19 (5%) expressed dissatisfaction with the service. Conclusion The implementation of a Web-based teleconsulting service in Colombia appeared to be an innovative way to improve access to health care and information in the community and encouraged open and explicit discussion. Extending the service to underserved areas could improve access to health services and health information and could potentially improve economic indicators such as waiting times for consultations and the rate of pregnancy among teenagers; however, cultural, infrastructural, and Internet connectivity barriers are to be solved before successful implementation can derive population-wide positive impacts.